2021
DOI: 10.1021/acschemneuro.1c00373
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahydropalmatine Regulates BDNF through TrkB/CAM Interaction to Alleviate the Neurotoxicity Induced by Methamphetamine

Abstract: Tetrahydropalmatine (THP) has analgesic, hypnotic, sedative, and other pharmacological effects. Brain-derived neurotrophic factor (BDNF) plays an important role in neuronal plasticity, growth, and development. However, their mechanism of action in methamphetamine (MA)-induced neurotoxicity remains unclear. This study aims to explore the important role of BDNF in MA neurotoxicity and whether THP can regulate BDNF through the interaction between tyrosine kinase receptor B (TrkB)/calmodulin (CAM) to alleviate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Since METH exposure can also lead to poor performances in other cognitive phenotypes, 35,37–39 we also conducted a Y‐maze test to further confirm the neuroprotective effects of KOR antagonist (Figure 7A,B). We found that METH decreased number (Figure 7E, F (2, 33) = 6.921, p = 0.0031) and rate of spontaneous alteration (SAP) (Figure 7F, F (2, 33) = 13.33, p < 0.0001) and increased incorrect same arms returns (SAR) (Figure 7D, F ((2, 33) = 4.995, p = 0.0127), which was reserved by norBNI microinjections into PL before METH treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since METH exposure can also lead to poor performances in other cognitive phenotypes, 35,37–39 we also conducted a Y‐maze test to further confirm the neuroprotective effects of KOR antagonist (Figure 7A,B). We found that METH decreased number (Figure 7E, F (2, 33) = 6.921, p = 0.0031) and rate of spontaneous alteration (SAP) (Figure 7F, F (2, 33) = 13.33, p < 0.0001) and increased incorrect same arms returns (SAR) (Figure 7D, F ((2, 33) = 4.995, p = 0.0127), which was reserved by norBNI microinjections into PL before METH treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Since METH exposure can also lead to poor performances in other cognitive phenotypes, 35,[37][38][39] we also conducted a Y-maze test to further confirm the neuroprotective effects of KOR antagonist (Figure 7A,B). We found that METH decreased number (Figure 7E, F The medial prefrontal cortex (mPFC) is a crucial brain region involved in cognition.…”
Section: Intra-pl But Not Il Injection Of Kor Antagonist Prevents Met...mentioning
confidence: 99%
“…BDNF reduces the apoptosis of neurons submitted to oxygen–glucose deprivation/reoxygenation [ 47 ] and promotes neuronal survival after neonatal hypoxic-ischemic encephalopathy [ 48 ]. Moreover, the manipulation of the BDNF/TrkB pathway contributes to reversing neuronal apoptosis and alleviating neurotoxicity induced by methamphetamine [ 23 ] and propofol [ 49 ]. The upregulation of miR-10b-5p results in the decrease of BDNF levels in mouse hippocampal neurogenesis and cognitive impairment model [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, manipulating BDNF pathways represents a viable treatment approach to a variety of neurological and psychiatric disorders [ 22 ]. Upregulation of BDNF has been demonstrated to inhibit neuronal apoptosis and alleviate neurotoxicity induced by methamphetamine [ 23 ]. Accordingly, we speculated whether DEX pretreatment can upregulate BDNF expression through miR-10b-5p to regulate neuronal viability and protect against ropivacaine-induced neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…A research report noted that rat brains exhibited significant increases in time- and location-dependent BNDF and NTRK2 expression following binge-like METH exposure (4 x 4 mg/kg, s.c., 2 h (h) apart) ( 34 ). Another study concluded that high expression of BDNF and NTRK2 contributed to the reduction of METH-induced apoptosis ( 35 ). Combined with the 2 studies, it is reasonable to speculate that the high concentration of circ_0015891 could sponge miR-615-5p to disinhibit NTRK2 ( Table 1 ), contributing to protect dopaminergic cells from apoptosis.…”
Section: Discussionmentioning
confidence: 99%